The relationship between body height and plantar pressure distribution in adult handball players: A cross-sectional study - Amr Almaz Abdel-aziem; Mariam A Ameer (Journal of Orthopaedics, Trauma and Rehabilitation)
Background/purpose The relationship between a handball player's upper body posture, body weight distribution in relation to body height is poorly understood. So, this study explored the relationship between body height and sagittal spinal curvatures and plantar pressure distribution in handball players. Method According to handball player's body height, 63 male handball players were divided into two groups; group A (age, 23.54 ± 1.32 years) consisted of 30 handball players with body height above average, and group B (age, 23.40 ± 1.73 years) consisted of 33 handball players with body height below average. The thoracic and lumbar curvatures and trunk height were measured with the Formetric III 4D spine, and the DIERS Pedoscan device was used to assess the plantar pressure distribution for both groups. Results The thoracic kyphosis of group A was significantly higher than that of group B ( p  = 0.001), without a significant difference in lumbar lordosis ( p  = 0.086). Group A showed a significant increase in the forefeet pressure and a significant decrease in the rearfeet pressure compared to group B ( p  = 0.001). There was a high positive correlation between the body height and trunk length, and body height and kyphosis angle ( r  = 0.932, r  = 0.665, respectively). There was a high positive correlation between the body height and forefoot plantar pressure ( r  = 0.665, p < 0.01). Conclusion The taller handball players have an increased thoracic kyphosis angle and forefeet pressure compared to shorter handball players.